2016
DOI: 10.5194/acp-2016-215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ozone Production and Its Sensitivity to NO<sub><i>x</i></sub> and VOCs: Results from the DISCOVER-AQ Field Experiment, Houston 2013

Abstract: <p><strong>Abstract.</strong> An observation-constrained box model based on the Carbon Bond mechanism, Version 5 (CB05), was used to study photochemical processes along the NASA P-3B flight track and spirals over eight surface sites during the September 2013 Houston, Texas deployment of the NASA DISCOVER-AQ campaign. Data from this campaign provided an opportunity to examine and improve our understanding of atmospheric photochemical oxidation processes related to the f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Thus, even though we are unable to pigeonhole the time‐dependent O 3 sensitivity at Moody Tower as being radical limited or NO x limited, one could still deduce that reducing NO x emissions, especially later in the day, would be effective for reducing local O 3 . It should be noted, however, that our conclusions about P(O 3 ) in Houston do not always agree with the results presented in a similar study, particularly in the morning [ Mazzuca et al ., ]. At Deer Park, for example, Mazzuca et al reported a morning median P(O 3 ) value of 30 ppbv/h, while we report a morning median value of 17.2 ppbv/h.…”
Section: Temporal Evolution Of P(o3) Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, even though we are unable to pigeonhole the time‐dependent O 3 sensitivity at Moody Tower as being radical limited or NO x limited, one could still deduce that reducing NO x emissions, especially later in the day, would be effective for reducing local O 3 . It should be noted, however, that our conclusions about P(O 3 ) in Houston do not always agree with the results presented in a similar study, particularly in the morning [ Mazzuca et al ., ]. At Deer Park, for example, Mazzuca et al reported a morning median P(O 3 ) value of 30 ppbv/h, while we report a morning median value of 17.2 ppbv/h.…”
Section: Temporal Evolution Of P(o3) Sensitivitymentioning
confidence: 99%
“…This discrepancy is also present at every other site (with the exception of Galveston and Conroe), where our modeled P(O 3 ) in the morning tends to be 5–10 ppbv/h lower than the reported values in Mazzuca et al . []. This discrepancy can be attributed to differences in model chemistry: In a previous ground‐based study conducted at Moody Tower, the Carbon Bond mechanism, version 5 (CB05, also used in Mazzuca et al .…”
Section: Temporal Evolution Of P(o3) Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Estimating the OPE as ∆O 3 /∆NO z is known to be an upper limit for describing how efficiently O 3 can be produced for multiple reasons. First, if there is considerable loss of NO z due to deposition of HNO 3 , the OPE is biased high (Mazzuca et al, ; Neuman et al, ; Trainer et al, , ). Second, approximating the OPE as ∆O 3 /∆NO z does not account for mixing and fresh emissions (Zaveri et al, ).…”
Section: Introductionmentioning
confidence: 99%